The Existence of Library Literacy in Indonesia in the Millennial Era: Strategies for Improving the Quality of Education to Support the Sustainable Development Goals (SDG's) - Ishmah Afiyah; Muthoifin (Walidem Institute and Publishing, 2025)
Objective: This study aims to analyze the existence of library literacy in Indonesia in the millennial era and investigate strategies to improve the quality of education in supporting the achievement of the Sustainable Development Goals (SDGs), especially those related to quality education and equal access to information. Library literacy plays an important role in improving individuals' ability to access, process, and utilize information effectively. Theoretical Framework: the one used in this study refers to the concept of information literacy and the role of libraries in education, as well as a sustainable development theory that links quality education to the achievement of the SDGs. Literature Review: The existing literature shows that despite efforts to improve access to information and education in Indonesia, the library literacy gap between regions is still a major challenge. Several studies highlight the lack of adequate library infrastructure, lack of training for library managers, and limited access to technology for people in remote areas. Methods: This study uses a qualitative method with a case study approach in several libraries located in large cities and remote areas. Data was collected through interviews with library managers, teachers, and students, as well as analysis of documents related to library literacy policies in Indonesia. Results: The results of the study show that library literacy in Indonesia in the millennial era faces several obstacles, including the lack of technological facilities in regional libraries, the low quality of human resource management in the library sector, and the unequal access to information in rural areas. However, there are also several positive initiatives carried out by the library community, such as digital literacy training for students and the introduction of mobile libraries. Implications: The implication of this study is the importance of strengthening policies that support the development of library infrastructure and the improvement of digital literacy skills, as part of a strategy to achieve the SDGs, especially in terms of inclusive and quality education. Novelty: The novelty of this research lies in integrating library literacy with the goal of sustainable development in the context of Indonesian education.